Implementing Democratic Learning Through Independent Learning - Marbun, Robinson; Siringo-ringo, Juspen; Nadeak, Devi; Siburian, Ivan (Sahabat Publikasi, 2024)
This article explores the application of a democratic learning approach through the concept of Freedom of Learning in the context of education. Through literature analysis and empirical studies, this article presents strategies and practices that support the development of student-centered learning, strengthen their active participation in the learning process, and encourage learning independence. The findings highlight the importance of understanding the concept of Freedom of Learning in the context of democratic education as well as the challenges and opportunities in applying it at various levels of education. The implications of this approach on improving the quality of learning and developing students' skills and attitudes were also discussed. In conclusion, this article emphasizes the importance of the Merdeka Learning approach in building an inclusive, participatory, and oriented learning environment that is oriented towards developing students' capacity as democratic citizens.